Молекулярная организация структуры сывороточного альбумина человека - Остоловский, Е.М.; Боцянский, А.Д.; Борисенко, С.Н.; Толкачева, Н.В. (Биополимеры и клетка, 1990)
С помощью комплекса физико-химических методов (ИК- и ЯМР-спектроскопия, круговой дихроизм и др.) в работе установлено, что молекула сывороточного альбумина человека представляет собой весьма компактную глобулу со значительным вкладом доли упорядоченных и неупорядоченных структур. За допомогою комплексу фізико-хімічних методів (ІЧ- і ЯМР-спектроскопія, круговий дихроїзм тощо) у роботі встановлено, що молекула сироваткового альбуміну людини є досить компактною глобулою зі значним внеском частки впорядкованих та невпорядкованих структур. Physicochemical methods (IR- and NMR-spectroscopy, circular dichroism, etc.) that human serum albumin molecule is a compact globule with 50 % spiral structure and with exposition of a half of tyrozil on its surface. At the same time considerable percent of polypeptide chain with disordely packed form and with small contribution of β-structure part is observed in the molecule space structure. Theoretical calculations of α-spiral parts localization in serum albumin molecule indicate that approximately equal number of amino acids residues is found in every of three domains.